The Epistemological Views of Grigor Tatevatsi - Zakaryan, Seyran (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
Saint Grigor Tatevatsi's (1346-1409) epistemological views have an optimistic nature: first, he does not doubt the real existence of the knowable created world and particular things, second, he is convinced that man has sufficient epistemic means to know existence. The supreme goal of cognition is the knowledge of God, so knowledge is valued according to its nature and orientation as well as its contribution to the salvation of the soul. Tatevatsi defends the fundamental proposition of Aristotelian epistemology: human knowledge is acquired, because there are no innate ideas and knowledge in human soul. Tatevatsi distinguishes three degrees of knowledge: sensual, rational and knowledge acquired through faith.  Although these have different objects, knowledge tools, methods and involve different abilities, together they ensure the integrity of human knowledge. Even though the knowing subject is generally passive, general concepts in the mind are formed in part thanks to the activity of the subject. He defines truth as the correspondence between thought and reality. Although Tatevatsi separates philosophical and theological truths, he does not support the teaching of "two truths". Philosophical propositions are true if they are consistent with the truths of Revelation.
Keywords: Grigor Tatevatsi; epistemology; means of cognation; sensual and rational degrees of cognation; faith; knowledge; truth; teaching of; universals